Navigating the New Era of SEO: Voice Search, AI, and User Intent - Kinanti, Lintang Anis Bena; I Gede Novian Suteja, Pramelani Pramelani, (YUME : Journal of Management, 2025)
The evolution of search engine optimization (SEO) in the digital era has been significantly influenced by the rise of artificial intelligence (AI), the increasing adoption of voice search technologies, and the growing emphasis on understanding user intent. This study explores how SEO professionals adapt to these transformations through a qualitative research design involving in-depth interviews with industry practitioners. Findings reveal that traditional keyword-based strategies are being replaced by AI-driven, intent-focused, and conversational content approaches. Key themes include the restructuring of content for voice search, the use of predictive analytics for intent modeling, and the integration of AI tools for content customization. Participants also identified critical challenges such as algorithm transparency, data privacy limitations, and the need to maintain human oversight in automated systems. The study concludes that the future of SEO lies in a balanced integration of AI capabilities and human strategic thinking, where adaptability, contextual relevance, and ethical considerations define successful digital visibility in an increasingly intelligent search environment. Keywords: Search Engine Optimization, Voice Search, Artificial Intelligence, User Intent, Digital Marketing, Content Strategy